EFFECTIVENESS OF TREATMENT FOR VERTEBRAL FRACTURES IN THE CONTEXT OF OSTEOPOROSIS - Gulnara Alautdinovna Alikhodjaeva; Xujanazarov Ilxom Eshqulovich; Ijod Rustamovich Alimov; Sherzod Jumnazarovich Kazakov (Scholar Express Journals, 2026)
Currently, a number of scientific studies are being conducted on the treatment of osteoporotic fractures of the vertebral body. Problems such as the causes of osteoporotic fractures of the vertebral body, the introduction of new diagnostic methods for their diagnosis, the effect of newly created drugs in conservative treatment, the duration of spinal immobilization, and the prevention of secondary complications in patients with long-term immobilization have been studied. A new surgical method of kyphoplasty has been developed to restore the strength of osteoporotic fractures of the vertebral body.
Keywords: Osteoporosis; osteoporotic vertebral fractures; percutaneous vertebroplasty